The integrated prediction system for geological conditions ahead of tunnel faces - S. Shirasagi, S. Shirasagi; T. Yamamoto, T. Yamamoto; Y. Mito, Y. Mito; M. Ashraf, M. Ashraf (2011)
It is essential to employ the observational design and construction method to manage tunnel projects efficiently.